Radiative impact of aerosols and water vapor and contribution to the ‎intensification of the Saharan Heat Low over West Africa‎. - (:unkn) unknown (My University, 2017)
This work aims at enhancing our ‎understanding of the radiative impact of ‎aerosols and water vapor on the dynamics ‎of the Saharan Heat Low (SHL) using a ‎combination of space-borne observations ‎‎(MODIS, OMI, CALIOP) and a radiative ‎transfer model (STREAMER). The mean ‎seasonal variability of aerosol optical depth ‎‎(AOD) and integrated water vapor content ‎‎(IWVC) over the Sahara, averaged over the ‎last 11 years, is found to be well correlated ‎with the seasonal evolution of the SHL. ‎After the onset of the SHL, the IWVC is ‎observed to increase steadily over the ‎Sahara while the AOD exhibits a localized ‎maximum during August associated with the ‎presence of deep convective systems ‎forming over the Hoggar Mountains.‎To estimate the seasonal radiative impact of ‎water vapor and desert aerosols, ‎STREAMER was used to calculate the net ‎monthly radiative budget from May to ‎September. Average monthly temperature ‎and humidity profiles obtained from the ‎European center for medium range weather ‎forecast (ECMWF) analyses and extinction ‎coefficient profiles derived from CALIOP ‎are used as input parameters for the model ‎calculation.‎Our work shows that the aerosols forcing in ‎the shortwave (SW) dominates the net ‎surface radiative budget, while water vapor ‎is the strongest player in terms of longwave ‎‎(LW) forcing. The SW and LW forcing ‎associated with aerosols and water vapor, ‎respectively, contribute to heating the lower ‎troposphere over the Sahara during the ‎summer (when the SHL is over the Sahara).‎ In turn, this heating intensifies the cyclonic ‎circulation of the SHL thereby leading to ‎enhanced advection of water vapor ‎towards the Sahara.‎Hence, analyzing the decadal trends of ‎water vapor in the Tropics and sub-Tropics ‎is important to increase knowledge of the ‎dynamics of the SHL, a pivotal feature of ‎the West African Monsoon syst
Keywords: African Research